Education on Diverse, Nutritious, Balanced, Safe, and Halal Diet Habits to Adolescents in Bandar Lampung - Murniati, Ktut; Indriani, Yaktiworo; Sari, Dewi Mulia (Indonesian Journal of Community Services Cel, 2023)
There are four health problems that are considered most often experienced by Indonesian adolescents, namely iron deficiency (anemia), disturbance of body growth (stunting), chronic energy deficiency (underweight), and obesity (overweight). This community services activity aims to provide information and education about diverse, nutritious, balanced, safe, and halal (beragam, bergizi, seimbang, aman, dan halal/B2SAH) diet habits and the impact of contemporary food and beverages on adolescents’ health in Bandar Lampung City. This activity was carried out at Daarul 'Ilmi Integrated Islamic High School (SMA IT) in Bandar Lampung City. The target participants were the 11th and 12th grade students of Daarul 'Ilmi High School. The methods used were extension, discussion, and monitoring. The results showed that the implementation of community services activity in this school have succeeded in increasing the knowledge and understanding of the participants on the B2SAH eating habits, namely from the moderate category to the good category after participating in the activity, and resulted in changes in students’ behavior in consuming contemporary food.